Performance Evaluation of Solar Adsorption Cooling Systems for Vaccine Preservation in Sub-Saharan Africa - (:unkn) unknown (My University, 2016)
An intermittent solar adsorption refrigerator can supply cold needed in third world countries, especially for vaccine and medicine preservation. This paper investigated theoretically the potential of solar adsorption refrigerators in Sub-Saharan Africa. The dynamic behavior of the system and its performance were assessed using real climatic conditions of four Sub-Saharan African sites. A refrigerator operating with activated carbon/methanol as a working pair was simulated using a 1-D mathematical model to investigate its dynamic optimization. The results showed that the best solar coefficient of performance (SCOP) was predicted in Garoua (Cameroon) and Beitbridge (Zimbabwe). The maximum specific cooling power (SCP) was achieved in Beitbridge (Zimbabwe). Under the climate of Lamu (Kenya), the system presented the lowest performance indices.
Keywords: African Research